DESAIN DAN FRAMEWORK MODEL KLASIFIKASI KEPUTUSAN SELEKSI PENGADUAN PERKARA KONSUMEN PADA BADAN PENYELESAIAN SENGKETA KONSUMEN - Syaukani, Muhammad (Jurnal informasi dan komputer, 2024)
This study develops the design and framework of a decision classification model for selecting consumer case complaints. This model accommodates the decision-making process on consumer cases involving the assembly and the chairman of the Consumer Dispute Resolution Agency (BPSK) playing a role in a decision. This study produces a design and framework of a decision classification model for the selection of consumer case complaints with the stages of the consumer case classification selection process completed with the Naïve Bayes Classifier and TOPSIS for the final decision stage of the consumer case while testing uses the Confusion Matrix.